Isotopic identification using Pulse Shape Analysis of current signals from silicon detectors: Recent results from the FAZIA collaboration - Pastore, G.; Gruyer, D.; Ottanelli, P.; Le Neindre, N.; Pasquali, G.; Alba, R.; Barlini, S.; Bini, M.; Bonnet, E.; Borderie, B.; Bougault, R.; Bruno, M.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2017)
The FAZIA apparatus exploits Pulse Shape Analysis (PSA) to identify nuclear fragments stopped in the first layer of a Silicon-Silicon-CsI(Tl) detector telescope. In this work, for the first time, we show that the isotopes of fragments having atomic number as high as Z∼20 can be identified. Such a remarkable result has been obtained thanks to a careful construction of the Si detectors and to the use of low noise and high performance digitizing electronics. Moreover, optimized PSA algorithms are needed. This work deals with the choice of the best algorithm for PSA of current signals. A smoothing spline algorithm is demonstrated to give optimal results without requiring too much computational resources.